colours - Sirett, Dawn (London Dorling Kindersley Limited, 2013)
Features bright photographs and 5 fun pop-out surprises. In this title, four toys have different favourite colours, and each one is looking for their friend. Teddy is searching for Yellow Ducky, who pops out of a yellow watering can. But where is Rabbit's friend, Blue Dragonfly, hiding?
Scientific notions
1 2 23
Keywords: Hide-and-seek -- Juvenile fiction; Play -- Juvenile fiction; Toy and movable books -- Specimens